A durable pollination raincoat for hybridization during monsoon in coconut - Devakumar, K.; Thomas, Regi Jacob; Karun, Anitha (Journal of Plantation Crops, 2020)
Large-scale production of hybrid seed nuts of coconut is necessary to match the high demand for hybrid seedlings. But in major coconut producing states such as Kerala, Karnataka and Goa hybridisation is carried suspended during monsoon season and out effectively only during dry season for a period of six months from November to May. Some of the reasons attributed to the stoppage of pollination work during monsoon are the slippage of the trunk while climbing, problems in male flower collection and wetting of the pollination bags during heavy rains. Technological developments in coconut sector viz., the invention of coconut climbing devices and cryopreservation techniques have contributed to safe climbing and pollen storage for utilisation during off-seasons, respectively. However, the wetting of the pollination bag used for hybridization remains a problem. We report the development and successful initial testing of a durable raincoat for the pollination bag so that coconut pollination can be carried out throughout the year in heavy monsoon areas. This reusable raincoat is integrated with the ground pollination unit and can be fitted easily on the pollination bag, and it ensures complete dryness of the pollination bag. Only one climbing per tree is required for emasculation, bagging and raincoat fitting on a single inflorescence. The raincoat has provisions for suspending a pollen delivery tube and pollen dusting and bag removal can be done from the ground. The durable raincoat cover for the pollination bags has resulted in a fruit setting of 22.5-41.3 per cent.